Características clínico-epidemiológicas de niños con bronquiolitis en ventilación no invasiva que conllevan al uso de ventilación mécanica invasiva, Hospital Iquitos, 2017-2019 - Panduro Vásquez, Indira Esther (2023)
Bronchiolitis is usually a self-limited disease, however, between 1 and 3% of patients are hospitalized and up to 15% of these may develop respiratory failure with increased work of breathing. Therefore, the present work aims to determine the clinical-epidemiological characteristics of children with bronchiolitis in non-invasive ventilation that lead to the use of invasive mechanical ventilation, Hospital Iquitos, 2017 - 2019. For this, an observational-analytical and cross-sectional study. The sample was 32 patients, concluding that the sex, age, origin, type of delivery, exclusive breastfeeding and clinical characteristics such as apnea, tachypnea, respiratory distress, nasal flaring, wheezing, retraction, fever did not present an association with the use of invasive mechanical ventilation (p>0.05). The patients who presented an incomplete vaccination schedule presented a statistically significant association with the use of invasive mechanical ventilation (p=0.038).